Analysis of Production Results of Clear Coffee Streamer Machines - Wardhana, Megandhi Gusti; Putra, Adi Pratama; Hadi, Charis Fathul; Anam, Muhamad Khoirul (Journal of Science Technology (JoSTec), 2024)
Indonesia is the fourth coffee producer in the world after Brazil, Vietnam and Colombia. However, in the 2018-2021 period, the value of Indonesian coffee exports experienced a decline, which was in line with the low volume of Indonesian coffee exports in that year compared to the previous period, so that Indonesia's position fell from fourth to fifth as a coffee exporting country in the world. These various things could be due to the lack of downstream processing in coffee processing in Indonesia. The current problem is that there is no tool for the process of separating coffee into clear coffee, this tool is available abroad and the price is quite expensive. This research tries to make a clear coffee streamer and analyzes the production results of a clear coffee streamer. The results of the design of a clear coffee streamer tool using stainless steel material can be used with a capacity of 20 liters and a maximum heating temperature of 100oC, while testing the production capacity of the clear coffee streamer tool produces data using a material volume of 1500 ml resulting in a production volume of 850 ml in a time of 75 minutes. Meanwhile, using a volume of 200 ml of material produces 950 ml with a time of 75 minutes.